2019
DOI: 10.3390/vision3040065
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptual and Aesthetic Aspects of the Music-Paintings Congruence

Abstract: The purpose of the present study is to investigate the effect of congruence between music and paintings on the aesthetic preference of paintings. Congruence was specified as the similarity in perceived regularity and the complexity of jazz compositions and abstract paintings (the ratings of regularity and complexity in both sets of stimuli were obtained in the pilot study). In the main experiment, 32 participants rated the aesthetic pleasantness of paintings with congruent, incongruent, and no music background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…This partial diversity between the two phases of the experiment may reveal a structural difference between the linguistic and the perceptual mediums adopted in the evaluations, which is important to bear in mind in the debate among synesthesia, cross-modality, and ideasthesia. This result suggests that the semantic differential methods, also used in other related studies (e.g., Rančić & Marković, 2019 ), might be insufficient to fully account for cross-modal correspondences, in particular for multimodal Gestalt effects.…”
Section: Discussionmentioning
confidence: 91%
“…This partial diversity between the two phases of the experiment may reveal a structural difference between the linguistic and the perceptual mediums adopted in the evaluations, which is important to bear in mind in the debate among synesthesia, cross-modality, and ideasthesia. This result suggests that the semantic differential methods, also used in other related studies (e.g., Rančić & Marković, 2019 ), might be insufficient to fully account for cross-modal correspondences, in particular for multimodal Gestalt effects.…”
Section: Discussionmentioning
confidence: 91%
“…Braun Janzen et al (2022) observed that in a genuine museum setting, both the valence of music and how pleasant it was for participants affected their appreciation for paintings. On the contrary, Rančić and Marković (2019) found no appreciation effect even when participants were able to identify the valence congruency between music and paintings. It is likely that these art-music interactions are colored by the widely discussed contextual and genuineness effects as well.…”
Section: Introductionmentioning
confidence: 73%
“…Crossmodal correspondence refers to the natural tendency to associate sensory features of a stimulus in one modality with a sensory feature in another modality, such as color/sound and shape/sound (Chen & Spence, 2017; Spence, 2011, 2020; Spence & Deroy, 2013). Stylistic congruences between music and visual artwork have been examined, with findings suggesting that stylistic music-painting matching relies primarily on judgments of stimuli complexity (Albertazzi et al, 2015; Marin et al, 2016; Marin & Leder, 2013; Rančić & Marković, 2019). Nevertheless, recent research suggests that stylistic congruence does not seem to impact the aesthetic experience (Rančić & Marković, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Stylistic congruences between music and visual artwork have been examined, with findings suggesting that stylistic music-painting matching relies primarily on judgments of stimuli complexity (Albertazzi et al, 2015; Marin et al, 2016; Marin & Leder, 2013; Rančić & Marković, 2019). Nevertheless, recent research suggests that stylistic congruence does not seem to impact the aesthetic experience (Rančić & Marković, 2019). Crossmodal correspondences between sound/music and other sensory modalities have also been reported, with findings suggesting that musical emotions can modulate consumers’ hedonic judgment of foods and beverages (Kantono et al, 2019; Reinoso-Carvalho et al, 2019; Spence et al, 2019; Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%